Application of metal cation-doped NiO catalyst in two-electron oxygen reduction reaction

By doping Fe and Zn in NiO catalysts and optimizing their structure and composition, the problem of insufficient catalyst activity and selectivity in the prior art is solved, and efficient, stable and low-cost hydrogen peroxide production is achieved, with broad industrial application prospects.

CN119710807AActive Publication Date: 2025-03-28KUNMING UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411917682.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The prior art has difficulties in developing efficient, selective and stable catalysts for electrochemical di-electron oxygen reduction reactions, especially in terms of cost-effectiveness and sustainability of metal resources.

Method used

The Zn-NiO and Fe-NiO catalysts were prepared by solution combustion using metal cation-doped NiO catalysts, and the composition and structure of the catalysts were optimized to improve their adsorption ability to OOH intermediates and their activity in the di-electron oxygen reduction reaction.

Benefits of technology

The production of hydrogen peroxide with high selectivity and activity is achieved, especially under alkaline conditions. Zn-NiO catalysts show excellent stability and high yield, reduce production costs and have industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005207194800000011
    Figure HDA0005207194800000011
  • Figure HDA0005207194800000012
    Figure HDA0005207194800000012
  • Figure HDA0005207194800000013
    Figure HDA0005207194800000013
Patent Text Reader

Abstract

The invention discloses an application of a metal cation doped NiO catalyst in a two-electron oxygen reduction reaction, wherein the metal comprises Fe and / or Zn. The invention discloses a preparation method of a metal cation doped NiO catalyst. The preparation method comprises the following steps: preparing Ni salt and a precursor solution doped with metal salt; and transferring the precursor solution to a muffle furnace for heating, and washing and drying a product to obtain the metal cation doped NiO catalyst. Through specific metal cation doping, the electrocatalytic activity and selectivity of the transition metal oxide NiO on 2e-ORR are changed from an electronic structure, and particularly, the Zn-NiO catalyst has high selectivity, activity and long-term stability on hydrogen peroxide production from 2e-ORR under an alkaline condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of two-electron oxygen reduction reaction catalysts; more specifically, it relates to the application of metal cation-doped NiO (nickel oxide) catalysts in two-electron oxygen reduction reactions. Background Art

[0002] Hydrogen peroxide (H2O2) is considered a green, versatile, and environmentally friendly oxidant with extensive applications in industries such as pulp and paper, food processing, water treatment, textiles, laundry, petroleum, and electronics. Historically, it has played a vital role as a disinfectant against SARS-CoV-2 during the COVID-19 pandemic. Currently, industrial production of H2O2 relies primarily on the energy-intensive and complex large-scale anthraquinone process, which raises concerns about environmental impact, cost, and safety. An alternative approach involves mixing gaseous hydrogen (H2) and oxygen (O2) directly over a precious metal-based catalyst. However, this approach poses safety challenges and requires additional precautions to mitigate the risk of hydrogen explosions.

[0003] Compared with these methods, electrochemical two-electron oxygen reduction (2e - ORR) is a green, efficient, economical, safe and flexible route to synthesize H2O2. In order to develop a highly selective, active, stable and cost-effective catalyst to reduce O2 to H2O2 instead of H2O, it is necessary to develop a catalyst with weak OO bond dissociation energy and sufficient oxidizing power to promote the generation of H2O2.

[0004] At present, some pioneering studies have identified precious metals and alloys as the main 2e - Highly efficient electrocatalysts for ORR have been proposed and have achieved promising results. However, their high price and scarcity of metal resources restrict their feasible production and application. In contrast, non-precious transition metal compounds, such as those based on tungsten (W), vanadium (V), nickel (Ni), molybdenum (Mo), and iron (Fe), including oxides, chalcogenides, phosphates, and single atoms, have many advantages. These advantages include their abundance in the Earth's crust, low cost, good environmental compatibility, and the ability to tune their composition and structure, thus showing promise as advanced 2e - Great potential of ORR electrocatalysts.

[0005] In recent years, transition metal oxide materials have been used as 2e - ORR catalysts have been extensively studied. Doping exogenous elements in appropriate metal oxide-based catalysts has become a promising approach to improve the 2e -A feasible strategy for ORR electrocatalytic performance. Element doping significantly changes the electronic structure of the original metal oxide, resulting in a narrower band gap, which is beneficial to improve conductivity. However, how to prepare 2e - Cation-doped oxide catalysts with better ORR electrocatalytic performance are still a technical challenge, especially the effect of different metal doping on 2e - There is still a lack of in-depth understanding of the influencing mechanisms and laws of ORR electrocatalytic performance. Summary of the invention

[0006] The invention discloses the application of a metal cation-doped NiO catalyst in a two-electron oxygen reduction reaction to achieve efficient and stable hydrogen peroxide production.

[0007] Specifically, the present invention relates to the use of metal cation-doped NiO catalysts in a two-electron oxygen reduction reaction; wherein the metal comprises Fe and / or Zn.

[0008] Furthermore, the preparation method of the metal cation-doped NiO catalyst comprises the following steps:

[0009] S1. Preparing a precursor solution of Ni salt and doped metal salt;

[0010] S2. The precursor solution is transferred to a muffle furnace for heating, and the product is washed and dried to obtain the metal cation-doped NiO catalyst.

[0011] Furthermore, the molar ratio of the Ni salt to the doping metal salt is 9:0.5-1.5.

[0012] Furthermore, step S1 includes: separately preparing a Ni salt solution and a doping metal salt solution, then first adding an appropriate amount of ethylene glycol to the Ni salt solution, and then mixing the two solutions in proportion.

[0013] Furthermore, the molar concentration of the Ni salt solution and the doping metal salt solution is 0.1-1M.

[0014] Furthermore, the mass ratio of ethylene glycol to metal Ni is 1:0.8-1.

[0015] Furthermore, the Ni salt is Ni(NO3)2 or NiCl2.

[0016] Furthermore, the doped metal salt is any one of Fe(NO3)3 or FeCl3 and Zn(NO3)2 or ZnCl2 or a combination thereof.

[0017] Furthermore, the temperature raising procedure of the muffle furnace in step S2 is: firstly heating to 100° C. at 5 to 15° C. / min, then heating to 300 to 400° C. at 1 to 5° C. / min and keeping the temperature for 0.5 to 2 hours.

[0018] Furthermore, the two-electron oxygen reduction reaction is carried out in an alkaline environment.

[0019] The technical solution of the present invention has the following beneficial effects:

[0020] The metal cation doped NiO catalyst used in the two-electron oxygen reduction reaction of the present invention is doped with Fe and / or Zn. This specific selection enables the catalyst to have the best adsorption energy for the OOH* intermediate, especially the Zn-NiO nanocatalyst has high selectivity, activity and long-term stability for the production of hydrogen peroxide under alkaline conditions. The metal cation doped NiO catalyst disclosed in the invention can be synthesized in large quantities using a solution combustion method, does not require harsh production conditions, has a simple preparation method, and can achieve low-cost industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 In the figure, a is the X-ray diffraction (XRD) pattern of the catalysts of the embodiment and the comparative example, and b is the XRD local enlarged pattern in the diffraction range of 40 to 45°;

[0022] Figure 2 is a scanning electron microscope (SEM) image of the Zn-NiO catalyst;

[0023] Figure 3 Middle: a and b are scanning electron microscope (SEM) images of Fe-NiO catalysts, c and d are SEM images of NiO catalysts, e and f are SEM images of Co-NiO catalysts, and g and h are SEM images of Cu-NiO catalysts;

[0024] Figure 4 Middle: a is the high-resolution transmission electron microscopy (HRTEM) image of NiO catalyst, b is the HRTEM image of Zn-NiO catalyst;

[0025] Figure 5 The X-ray photoelectron spectroscopy (XPS) spectra of the catalysts of the examples and comparative examples;

[0026] Figure 6 Ni2p, X-ray photoelectron spectroscopy (XPS) spectra of the catalysts of the examples and comparative examples;

[0027] Figure 7 The O1s X-ray photoelectron spectroscopy (XPS) spectra of the catalysts of the examples and comparative examples;

[0028] Figure 8 The (Zn, Fe, Cu, Co) 2p X-ray photoelectron spectroscopy (XPS) spectra of the catalysts of the examples and comparative examples;

[0029] Fig. 9The Raman spectra of the catalysts of the embodiments and comparative examples are shown in FIG.

[0030] Fig.10 X-ray near edge absorption spectra (XANES) of Ni-K edge of catalysts of Examples and Comparative Examples;

[0031] Fig.11 Ni-K edge extended X-ray absorption fine structure spectra (EXAFS) of the catalysts of the examples and comparative examples;

[0032] Fig.12 Cyclic voltammetry (CV) spectra of the catalysts of the examples and comparative examples under nitrogen and oxygen saturation and 0.1 M KOH conditions, respectively;

[0033] Fig.13 The polarization curves (LSV) of the catalysts of the examples and comparative examples under nitrogen and oxygen saturation and 0.1 M KOH conditions, respectively;

[0034] Fig.14 The selectivity graphs of the catalysts of the examples and comparative examples to hydrogen peroxide under the conditions of nitrogen and oxygen saturation and 0.1 M KOH, respectively;

[0035] Fig.15 The electron transfer graphs of the catalysts of the examples and comparative examples to hydrogen peroxide under the conditions of nitrogen and oxygen saturation and 0.1M KOH, respectively;

[0036] Fig.16 The electrochemical impedance spectroscopy (EIS) graphs of the two-electron oxygen reduction reaction of the catalysts of the examples and comparative examples;

[0037] Fig.17 The stability and yield of Zn-NiO catalyst for preparing hydrogen peroxide by two-electron oxygen reduction reaction under 0.1M KOH condition and 0.4V vs. RHE voltage for 120h;

[0038] Fig.18 The stability and yield of Fe-NiO catalyst in the two-electron oxygen reduction reaction for preparing hydrogen peroxide at 0.4 V vs. RHE voltage for 12 h.

[0039] Fig.19 The stability and yield of Cu-NiO catalyst in 0.1M KOH at 0.4V vs. RHE for 12 hours to produce hydrogen peroxide by two-electron oxygen reduction reaction;

[0040] Fig. 20 The stability and yield of Co-NiO catalyst for preparing hydrogen peroxide by two-electron oxygen reduction reaction under 0.1M KOH condition and 0.4V vs. RHE voltage for 12h;

[0041] Fig.21 The stability and yield of NiO catalyst in 0.1M KOH at 0.4V vs. RHE for 12 hours to produce hydrogen peroxide by two-electron oxygen reduction reaction;

[0042] Fig. 22 The cyclic voltammetry (CV) spectra and double layer capacitance (C dl );

[0043] Fig.23 Middle: a is the electrophilic index diagram of the Zn-NiO catalyst, b is the two-electron oxygen reduction selectivity and H2O2 yield of the catalysts of the embodiment and the comparative example as a function of the d-band center;

[0044] Fig.24 Middle: a is the 2e of Zn-NiO and NiO catalysts - Comparison of ORR Gibbs free energy, b is the 2e of NiO catalyst - ORR and 4e - Comparison of ORR Gibbs free energy, c is the 2e of Zn-NiO catalyst - ORR and 4e - ORR Gibbs free energy comparison diagram, d is 2e on Zn-NiO - ORR and 4e - Schematic diagram of the ORR reaction pathway. DETAILED DESCRIPTION

[0045] The present invention will be further described below in conjunction with the accompanying drawings and specific implementation methods.

[0046] Example 1

[0047] Example 1 relates to a Zn-NiO catalyst, and its preparation method comprises the following specific steps:

[0048] First, a 0.5M equimolar solution of Ni(NO3)2 and ZnCl2 was prepared, and then a certain amount of ethylene glycol (EG) was added to the Ni(NO3)2 solution, and the mass ratio of EG to metal Ni was maintained at 1:0.95. 9mL of Ni(NO3)2-EG solution was mixed with 1mL of ZnCl2 dopant solution to obtain a precursor solution (wherein the molar ratio of Ni to Zn was 9:1.03), and the precursor solution was vigorously stirred for 1 hour.

[0049] The stirred solution was placed in a porcelain crucible and transferred to a muffle furnace for heating. The temperature rise program of the muffle furnace was: heated to 100°C at 10°C / min, then heated to 350°C at a rate of 2°C / min, and maintained at 350°C for 1 hour. The product was washed three times with deionized water and ethanol, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain the Zn-NiO catalyst.

[0050] Example 2

[0051] Example 2 relates to an Fe-NiO catalyst, and its preparation method is to replace the "0.5M ZnCl2 equimolar solution" described in Example 1 with "0.5M FeCl3 equimolar solution", and the other steps are the same as Example 1 to obtain the Fe-NiO catalyst.

[0052] Comparative Example 1

[0053] Comparative Example 1 involves a NiO catalyst, and its preparation method is to replace the "0.5M ZnCl2 equimolar solution" described in Example 1 with "0.5M Ni(NO3)2", and the other steps are the same as Example 1 to obtain the NiO catalyst.

[0054] Comparative Example 2

[0055] Comparative Example 2 involves a Cu-NiO catalyst, and its preparation method is to replace the "0.5M ZnCl2 equimolar solution" described in Example 1 with "0.5M CuCl2 equimolar solution", and the other steps are the same as Example 1 to obtain the Cu-NiO catalyst.

[0056] Comparative Example 3

[0057] Comparative Example 3 involves a Co-NiO catalyst, and its preparation method is to replace the "0.5M ZnCl2 equimolar solution" described in Example 1 with "0.5M CoCl2 equimolar solution", and the other steps are the same as Example 1 to obtain the Co-NiO catalyst.

[0058] Structural characterization and performance testing

[0059] Figure 1 a shows the XRD spectra of Zn-NiO, Fe-NiO, NiO, Cu-NiO, and Co-NiO, where the characteristic peaks at 37.28°, 43.27°, 62.87°, 75.41°, and 79.40° correspond to the (111), (200), (220), (110), and (222) planes of NiO, respectively, which fully match the JCPDS card number 47-1049. The synthesized NiO has a face-centered cubic (fcc) structure, and no additional impurity peaks related to other oxides are detected in the M-NiO (M = Zn, Fe, Cu, or Co) samples. Figure 1b shows that the diffraction peak of the (200) crystal plane shifts after metal doping, indicating that the metal is successfully doped into the NiO lattice.

[0060] Figure 2 shows the SEM image of Zn-NiO, Figure 3 SEM images of Fe-NiO (a and b), NiO (c and d), Co-NiO (e and f), and Cu-NiO (g and h) are shown. All NiOs show the morphology of nanoparticles. Different nanoparticle catalysts have different particle sizes, so C dl ( Fig. 22 ae) to evaluate the electrochemically active surface area ECSA, such as Fig. 22 f, the slightly different values ​​indicate that the ECSAs of several oxides are relatively similar, the size has little effect on different catalysts, and the main factor affecting their two-electron oxygen reduction ability is the different electronic structures of different transition metal oxides. Figure 4 In a, the lattice planes with a spacing of 0.209 nm are attributed to the (200) plane of NiO; Figure 4 In b, the lattice planes with a spacing of 0.213 nm are attributed to the (200) plane of Zn-NiO, further proving that Zn metal ions are successfully introduced into the NiO lattice.

[0061] like Figure 5 As shown, the full XPS spectrum clearly shows the presence of oxygen and corresponding metal elements in various catalysts, without any detectable impurity peaks, indicating that the synthesized oxides are of high purity. Figure 6 The high-resolution Ni 2p spectra of M-NiO and NiO are given. 2+ The peaks are located at 853.90eV and 871.52eV, while Ni 3+ The peaks are located at 855.64eV and 873.46eV, Ni 3+ Related to surface hydroxylation. Figure 7 The high-resolution O1s spectra of M-NiO and NiO are shown in Figure 2. In the high-resolution O1s spectrum of NiO, the two obvious peaks at 529.53 eV and 531.17 eV correspond to the lattice oxygen and the surface OH oxygen, respectively. Figure 8 As shown in the figure, the Zn 2p spectrum in Zn-NiO, the Fe 2p spectrum in Fe-NiO, the Cu 2p spectrum in Cu-NiO and the Co2p spectrum in Co-NiO are given. The addition of Cu and Co metals to nickel oxide forms localized Ni-O-Cu and Ni-O-Co active site structures. The Ni-O-Cu structure will lead to the annihilation of the intermediate OOH*, while Ni-O-Co is more inclined to undergo a four-electron oxygen reduction reaction, which has an impact on the 2e -The addition of Zn and Fe metals to nickel oxide is beneficial to the transfer of electrons, forming a localized Ni-O-Zn and Ni-O-Fe active site structure, which is beneficial to improve the 2e - ORR activity.

[0062] like Fig. 9 As shown in Figure 2, Raman spectra show the Ni-O stretching vibration modes of NiO catalysts doped and undoped with different transition metal cations. The Ni-O stretching modes of doped and undoped NiO catalysts are around 470-600 cm -1 Ni-O in Co (~524cm -1 )、Cu(~521cm -1 )、Fe(~562cm -1 ) and Zn-doped samples (~493 cm -1 ) is similar to the undoped sample (~481 cm -1 ) shows a blue shift compared to the stretching frequency in the Ni-O. This blue shift in the Ni-O stretching frequency is attributed to the incorporation of metal cations into nickel oxide, replacing a portion of Ni, thereby forming metal-oxygen bonds and changing the electronic structure.

[0063] Fig.10 The X-ray absorption near-edge spectra (XANES) of NiO catalysts doped and undoped with different transition metal cations are shown, and the fitting results indicate that the Ni valence state of M-NiO decreases and is between that of Ni foil and NiO, which is due to the increase in the electron density of Ni atoms caused by the incorporation of cations. Fig.11 The k-edge extended X-ray absorption fine structure (EXAFS) oscillation of Ni in the solution shows a typical peak of Ni-O bond at Around (phase uncorrected). When doped with cations, the NiO bond length increases slightly.

[0064] To evaluate the metal cation-doped NiO catalysts for 2e - The electrocatalytic performance of the ORR reaction was studied by using NiO catalysts doped with or without different transition metal cations to make anode catalytic electrodes, using a platinum electrode as the cathode and a KOH solution with a concentration of 0.1 mol / L as the electrolyte for electrochemical testing.

[0065] like Fig.12 As shown, in N2 and O2 saturated 0.1 M KOH electrolyte, at 50 mV s -1 The cyclic voltammetry (CV) curves of Zn-NiO, Fe-NiO, Cu-NiO, Co-NiO, and NiO catalysts were obtained at a low scan rate of . The results show that there is a strong oxygen reduction peak in the oxygen-saturated electrolyte, but not in nitrogen. At 0.5V (Vs. RHE) is attributed to the oxidation of H2O2, indicating that 2e - The preparation of H2O2 during the ORR process was successful.

[0066] Fig.13 Polarization curves of Zn-NiO, Fe-NiO, Cu-NiO, Co-NiO, and NiO catalysts. The ring currents related to H2O2 synthesis of different catalysts are very different. Among them, Zn-NiO shows the highest ring current, followed by Fe-NiO, both of which are higher than the other three comparative catalysts.

[0067] like Fig.15 As shown in the figure, the selectivity of NiO catalyst and M-NiO catalyst loaded on RRDE disk for H2O2 was calculated. Among them, Zn-NiO maintained a selectivity of about 93% at 0.1-0.5V vs. RHE, and the selectivity of Fe-NiO was 91%, which was much higher than Cu-NiO (82%), Co-NiO (67%) and NiO (84%), indicating that Zn-NiO has the best 2e - ORR activity.

[0068] like Fig.15 As shown, at 0.1-0.5V vs. RHE, the number of transferred electrons of Zn-NiO, Fe-NiO, Cu-NiO, Co-NiO, and NiO catalysts were calculated respectively, among which Zn-NiO had the highest number of transferred electrons (about 2.13) among all samples, indicating that in actual production, Zn-NiO can maintain good production capacity for hydrogen peroxide.

[0069] like Fig.16 As shown, the electrochemical impedance spectroscopy (EIS) of Zn-NiO, Fe-NiO, Cu-NiO, Co-NiO, and NiO is shown. Zn-NiO exhibits higher charge transfer rate and current density. Previous studies have shown that the exposure and conductivity of active sites determine the charge transfer resistance (Rct).

[0070] like Figure 17-21 As shown in the figure, the hydrogen peroxide yields of Zn-NiO, Fe-NiO, Cu-NiO, Co-NiO, and NiO were further tested, among which Zn-NiO showed a hydrogen peroxide yield of 514.59 mmol g at 0.4 V vs. RHE. -1 h -1The highest yield is much higher than that of Cu-NiO, Co-NiO and NiO, indicating that Zn-NiO can accumulate high-concentration hydrogen peroxide faster in practical applications. The yield of Zn-NiO in a 25ml electrolytic cell for 120 hours is almost unchanged, indicating its excellent stability, which means that Zn-NiO can be used in the actual production of hydrogen peroxide.

[0071] like Fig.23 As shown in a, the electrophilic index of Ni sites in Zn-NiO increases. With the incorporation of Zn, electrons are transferred through the Ni-O-Zn bridge, resulting in an increase in the charge density of certain Ni sites. Ni, as an active site, weakens the adsorption of the key intermediate *OOH. At the same time, Fig.23 As shown in b, as the d-band center of different doped metals moves away from the Fermi level, 2e - The selectivity of ORR and the yield of H2O2 increased, with Zn-NiO showing the best 2e - ORR selectivity and excellent H2O2 yield.

[0072] like Fig.24 As shown in Figure 2, the Gibbs free energy of the reaction paths of Zn-NiO and NiO catalysts was thermodynamically calculated. The results show that both catalysts exhibit the same potential-determining step (PDS), that is, the reduction of *OOH to H2O2. The PDS Gibbs free energy change of Zn-NiO is smaller than that of NiO, which is 2.182 eV. This indicates that the 2e - The thermodynamics of ORR are more favorable. In addition, the 2e - and 4e - The response trend between ORR. 2e of the two catalysts - ORR Gibbs free energy change PDS is less than 4e - ORR, indicating that both catalysts prefer 2e - ORR. Theoretical calculation results show that Zn-NiO has the best adsorption energy for the key intermediate *OOH and is more thermodynamically favorable to 2e - The occurrence of ORR was consistent with the experimental results.

[0073] Based on the above analysis, the doping of Zn and Fe is beneficial to improve the NiO - The electrocatalytic performance of ORR is significantly improved by the addition of Cu and Co, while the doping of Zn-NiO catalysts has the opposite effect. - The ORR reaction for preparing hydrogen peroxide has excellent catalytic activity and selectivity, and can meet the concentration of hydrogen peroxide required in daily life.

[0074] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. Application of metal cation doped NiO catalyst in two-electron oxygen reduction reaction, characterized in that: The metal includes Fe and / or Zn.

2. The use according to claim 1, characterized in that The preparation method of the metal cation-doped NiO catalyst comprises the following steps: S1, preparing a precursor solution of Ni salt and doped metal salt; S2. The precursor solution is transferred to a muffle furnace for heating, and the product is washed and dried to obtain the metal cation-doped NiO catalyst.

3. The use according to claim 2, characterized in that: The molar ratio of the Ni salt to the doping metal salt is 9:0.5-1.

5.

4. The use according to claim 2, characterized in that Step S1 includes: preparing a Ni salt solution and a doping metal salt solution respectively, then adding an appropriate amount of ethylene glycol to the Ni salt solution, and then mixing the two solutions in proportion.

5. The use according to claim 4, characterized in that: The molar concentration of the Ni salt solution and the doping metal salt solution is 0.1-1M.

6. The use according to claim 4, characterized in that: The mass ratio of ethylene glycol to metal Ni is 1:0.8-1.

7. The use according to claim 3, characterized in that: The Ni salt is Ni(NO3)2 or NiCl2.

8. The use according to claim 3, characterized in that: The doped metal salt is any one of Fe(NO3)3 or FeCl3 and Zn(NO3)2 or ZnCl2 or a combination thereof.

9. The use according to claim 2, characterized in that: The temperature raising procedure of the muffle furnace in step S2 is: firstly heating to 100° C. at 5-15° C. / min, then heating to 300-400° C. at 1-5° C. / min and keeping the temperature for 0.5-2 hours.

10. The use according to claim 1, characterized in that: The two-electron oxygen reduction reaction is carried out in an alkaline environment.

Citation Information

Patent Citations

  • Super capacitor material NiO synthesis method

    CN101570349A

  • Fe doped NiO composite material and semiconductor gas-sensitive element

    CN107399767A

  • Heterogeneous element doped perovskite type oxygen reduction electrocatalyst as well as preparation and application thereof

    CN114875431A

  • Preparation method of ferrous iron doped nickel hydroxide heterojunction catalyst

    CN117737778A